Hepatitis B Therapeutic Vaccine: A Patent Review - Shuaibu Abdullahi Hudu; Abdulgafar Olayiwola Jimoh; Kasimu Ghandi Ibrahim; Ahmed Subeh Alshrari (MDPI AG, 2022)
Viral hepatitis has long been underrated as a danger to global health. The UN only recently called for worldwide action to tackle viral hepatitis and lessen the disease burden in its "2030 Agenda for Sustainable Development". Hepatitis B virus (HBV), which causes liver cirrhosis and malignancy, is a main cause of death globally. This review analyses innovative HBV therapeutic vaccine candidates for which a patent was filed between January 2010 and March 2022 and presents future improvement techniques for vaccine efficacy. Although there is a preventative vaccine for HBV infection, over 3% of people worldwide have the disease on a long-term basis and can no longer benefit from it. Most people will have chronic HBV infection for the rest of their lives once it has been diagnosed. Moreover, only a small percentage of treated patients experience a functional cure with persistent hepatitis B surface antigen reduction. A significant proportion of deaths are caused by liver cirrhosis and hepatocellular cancer, which are both caused by chronic hepatitis B infection. Hence, there is an urgent need for novel medications due to the inadequacies of the current therapies.